Automatic and high-quality surface mesh generation for CAD models. (April 2019) - Guo, Jianwei; Ding, Fan; Jia, Xiaohong; Yan, Dong-Ming
Abstract: In this paper, we present a fully automatic framework that tessellates industrial computer-aided design (CAD) models into high-quality triangular meshes. In contrast to previous approaches that are purely parametric or performed directly in 3D space, our method is based on a remeshing algorithm that can achieve accuracy and high-quality simultaneously. Given an input standard CAD model, which is represented by B-rep format, we first rebuild the parametric domain for each surface patch according to an initial triangulation, and then the boundaries of the parametric domain are retriangulated by exploiting the Constrained Delaunay Triangulation (CDT). In the second stage, the 2D triangulation is projected back to the 3D space, and a modified global isotropic remeshing process is applied, which further improves the regularity and angle quality of the tessellated meshes. Experiments demonstrate the validity of the proposed approach and its ability to generate high-quality meshes. Moreover, we evaluate our technique and compare it with state-of-the-art CAD model tessellation approaches. Highlights: An automatic surface tessellation framework for complex industrial CAD models. Improvement of previous remeshing approach to generate high-quality surface meshes. Introduction of simple yet effective heuristics to merge the small patches.